Private equity challenge - evaluating Calavo growers´ attractiveness for an Lbo - Braga, Eduardo Tiago (2021)
This Work Project is an individual part of Investment Committee Paper on Calavo Growers, an American fresh fruit and health yon-the-go fresh food developed by a group of Master’s in Finance. The company is divided in to three segments: Fresh Products-which handles avocados and other fresh fruits; Calavo Foods–produces processed avocado products suchas guacamole; and RFG–a producer of a portfolio healthy foods suchas fresh-cut fruits. This individual component analyses the markets in which Calavo operates as wellthe investment thesis for the company and an initial overview of the value creation strategies that will be pursued.